Routine Probiotic Use in Very Preterm Infants: Retrospective Comparison of Two Cohorts - Bonsante, Francesco; Iacobelli, Silvia; Gouyon, Jean-Bernard (American Journal of Perinatology, 2013)
Objective Evidence supports the efficacy of probiotics in reducing necrotizing enterocolitis (NEC) in very low-birth-weight infants, although concerns remain with regard to their routine use. Since 2008 in our neonatal intensive care unit, a low dose of probiotics (unique strain) is administered as standard of care in all preterm babies born at 24 to 31 weeks' gestation. This study reports outcomes in infants receiving probiotic cohort (PC) compared with the historical cohort.Design Treatment with Lactobacillus rhamnosus Lcr35 (Lcr Restituo) (2 × 108 colony-forming units/12 h) was started early after birth and intention to treat was up to 36 weeks' gestation. The main outcome was definite NEC. Secondary outcomes were mortality, late-onset sepsis (LOS), cholestasis, isolated rectal bleeding (IRB), and time to reach full enteral feeding (FEF).Results A total of 1130 patients were included. No adverse effects were observed. Infants in PC presented a reduced rate of NEC (odds ratio [OR] 0.20; 95% confidence interval [CI] 0.07 to 0.58), mortality (OR 0.46; 95% CI 0.21 to 1.00), and LOS (OR 0.60; 95% CI 0.40 to 0.89) and achieved FEF significantly earlier. IRB was significantly reduced among infants receiving the complete scheduled treatment.Conclusion Administration of Lcr Restituo was well tolerated and associated with lower mortality and morbidities in this cohort. Our results provide evidence in support of the hypothesis that this probiotic may reduce IRB.
Keywords: VLBWI; preterm birth; probiotics; NEC; enteral nutrition; NICU; Lactobacillus casei rhamnosus 35 (Lcr Restituo)